Accessibility and Responsibility: Use of Generative AI by Ukrainian Students - Sharov, Sergii; Tereshchuk, Serhii; Romas, Liudmyla; Zemlianska, Alina; Derkachova, Olga; Saregar, Antomi; Шаров, Сергій Володимирович (Novi Pazar : UIKTEN, 2025)
EN: The article highlights the results of a survey of students at Ukrainian universities on the use of artificial intelligence (AI) systems in the educational process. The main advantages and risks of using generative AI in education have been analyzed. For collecting data, a questionnaire created with Google Forms was used. There were 177 students from different regions of Ukraine who participated in the survey. It has been found that the vast majority of respondents (94.4%) use AI to perform various educational tasks. The most common AI services among students turned out to be ChatGPT, Gemini, MidJourney and DALL-E. It has been found that Ukrainian teachers allow the use of ChatGPT in classes with certain restrictions and instructions. 90.4% of students adhere to the principles of academic integrity and process the text generated by ChatGPT.   Further research is planned to determine the possibilities of ChatGPT for developing critical thinking through reading and writing.
Keywords: generative artificial intelligence; ChatGPT; student; learning process; academic integrity; штучний інтелект; студент; навчальний процес; академічна доброчесність